Sustainable animal agriculture and crisis mitigation in livestock-dependent systems in southern Africa - Banda, J.W.; Chagunda, Mizeck G.G.; Kamwanja, L.A.; Phoya, R.K.D; Safalaoh, A.C.L. (Bunda College of Agriculture, 2001)
These proceedings contain papers, abstracts and posters of the Regional Conference on Sustainable Animal Agriculture and Crisis Mitigation in Livestock-dependent Systems in Southern Africa that took place at Malawi Institute of Management (MIM) in Lilongwe, Malawi, from 30th October to 1st November 2000. A keynote paper opens each theme and is followed by scientific contributions, short communications, and abstracts. Posters are published as short communications and/or abstracts. These proceedings are organised as follows: